Effects of GnRH agonist treatment on steroidogenesis and folliculogenesis in the ovary of cyclic mice - Singh Padmasana; Krishna Amitabh (BMC, 2010)
Abstract Background GnRH analogs (both agonist and antagonist) have been extensively used for clinical applications, following the discovery of its direct effects on ovary. With regard to the direct actions of GnRH agonist on ovary, conflicting data are reported. The mechanism through which GnRH agonist affect gonadal functions is still obscure. The aim of present study was thus to investigate the effects of treatment with different doses of GnRH agonist, in vivo and in vitro, on morphological, physiological and functional changes in the ovary of cyclic mice. Methods To find out the effect of GnRH agonist on ovarian activity, cyclic mice were treated with different doses for 8 days and its effect on folliculogenesis (morphological changes in follicle, Estrogen receptor, progesterone receptor), steroidogenesis (circulating progesterone level, StAR, LH-receptor, 3β-HSD), luteinization (Morphology of corpus luteum) and apoptosis (caspase-3, PARP) were observed. To find the in vitro effects of GnRH agonist with or without LH on ovary of mice, changes in the expression of LH-receptor, estrogen receptor, progesterone receptor, 3β-HSD in the ovary and progesterone level in the culture media were investigated. Results GnRH agonist treatment produced significant changes in ovarian mass, circulating steroids level and ovarian follicular development, steroidogenesis and apoptosis in the mice. GnRH agonist also caused dose dependent histological changes in follicular development and luteinization. The mice treated with different doses of GnRH agonist showed biphasic effects on steroid synthesis due to its effects on ovarian expression of LH-receptor, StAR, and 3β -hydroxysteroid dehydrogenase proteins. The high dose showed stimulatory effect, whereas pharmacological dose showed inhibitory effect on ovarian follicular development and steroidogenesis. The in vitro study generally showed inhibitory effects of GnRH agonist on ovarian activities, which may be reversed by the presence of LH. Conclusion Both inhibitory and stimulatory effects found in the present study suggest that GnRH agonist is a versatile tool in the therapy of a variety of gynecological and non-gynecological conditions. This study suggests that the outcome of direct effect of GnRH-ag on ovary depends on LH-responsiveness.